Sistem Bagi Hasil Pertanian di Desa Mengen Kecamatan Tamanan Kabupaten Bondowoso dalam Perspektif Ekonomi Islam - Zainul Anwar; Makkiyatul Mukarromah (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2023)
Business and work activities are strongly influenced by the conditions of an area, where people live and live. In rural areas, people generally depend on agriculture and rice fields for their livelihood. As in Mengen Village, Tamanan District, Bondowoso Regency, which is the location of this research, most of the people are engaged in agriculture, because the structure of the area is very suitable for the growth requirements of plants such as rice, vegetables, and the like. One way that is done by the community is by way of cooperation, because there are landowners who have several plots of land but cannot work on them for some reason so that the cultivators are represented by other people. Whereas in the distribution of the results it is divided each time of harvest, but sometimes in determining the distribution of the results there are parties who are disadvantaged, namely the land owner, because if there is a loss the cultivator does not want to know, the harvest is a profit or a loss, so this makes it not in accordance with Islamic economic views, because there is a tendency for one of the parties to be harmed. Therefore this research is to find out how the agricultural profit-sharing system is and whether the profit-sharing system is in accordance with the perspective of Islamic economics. The type of research method used is descriptive qualitative which uses field research methods (primary data) and library research (secondary data). Primary data is data taken from the first source in the field, namely landowners and sharecroppers, while secondary data is obtained from literature studies by reading books and journals related to these problems. Based on the results obtained, the agricultural profit-sharing system in Mengen village is that the land owner provides seeds and costs, while sharecroppers provide the tools and work used to work on the land, then the harvest is divided based on the agreement of both parties at the beginning of the contract, namely 1/5 than 100% or 80:20, and the distribution of the harvest is in accordance with Islamic economic principles.